PENGARUH GAYA HIDUP, CITRA MEREK, SOSIAL, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN TAS BRANDED KW - Bora, Sabike Tabitha; Rahmawan, Ginanjar (Globalwriting Academica Consulting & Publishing, 2022)
This research will be carried out with the aim of being able to find out how the influence of brand image, lifestyle, price & social environment on purchasing decisions of KW branded bags in the city of Surakarta. This research falls into the category of causal associative research using a quantitative approach. This study will use a questionnaire to obtain primary data using a 5-level Likert scale. The sampling technique used was purposive sampling with a total sample of 100 respondents. The results of this study indicate that brand image, lifestyle, social environment, and product quality have a significant influence on the decision to buy KW branded bags in Surakarta.